2019
DOI: 10.1007/978-3-030-22176-8_1
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-method Assessment of Risk and Protective Factors in Family Violence: Comparing Italian and Migrant Families

Abstract: Child maltreatment is a major public health issue, which threatens psychophysical well-being of almost 100,000 minors in Italy. The prevalence and social burden of this issue clearly indicate the need for preventive efforts, early identification of victimized children, and a rapid risk assessment of families referred to Child Protection Services (CPS). The present chapter proposes an evidence-based multi-method assessment system, specific for highlighting risk and protective factors in family functioning. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It should be noted that not all maltreatment cases are detected and registered with RCCRC, with research revealing that official records underestimate the prevalence of child maltreatment [ 4 , 37 , 38 ]. Moreover, some groups, such as unmarried and young mothers, may be overrepresented among RCCRC registration cases due to social class bias or social disadvantages [ 39 , 40 ], especially with a lack of fixed standards for RCCRC registration [ 41 ]. On the other hand, these mothers might actually have a higher risk for child maltreatment, as some previous studies suggested [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that not all maltreatment cases are detected and registered with RCCRC, with research revealing that official records underestimate the prevalence of child maltreatment [ 4 , 37 , 38 ]. Moreover, some groups, such as unmarried and young mothers, may be overrepresented among RCCRC registration cases due to social class bias or social disadvantages [ 39 , 40 ], especially with a lack of fixed standards for RCCRC registration [ 41 ]. On the other hand, these mothers might actually have a higher risk for child maltreatment, as some previous studies suggested [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study constitutes a second-level analysis of a larger project about the assessment of parents referred for child maltreatment (Milani, Miragoli, Grumi, & Di Blasio, 2020). This is especially focused on families where witnessed violence was detected; therefore, analyses were run on this specific subsample.…”
Section: Methodsmentioning
confidence: 99%